Intravital microscopy: Imaging host–parasite interactions in lymphoid organs. (7th November 2019) - De Niz, Mariana; Meehan, Gavin R.; Tavares, Joana
Abstract: Intravital microscopy allows imaging of biological phenomena within living animals, including host–parasite interactions. This has advanced our understanding of both, the function of lymphoid organs during parasitic infections, and the effect of parasites on such organs to allow their survival. In parasitic research, recent developments in this technique have been crucial for the direct study of host–parasite interactions within organs at depths, speeds and resolution previously difficult to achieve. Lymphoid organs have gained more attention as we start to understand their function during parasitic infections and the effect of parasites on them. In this review, we summarise technical and biological findings achieved by intravital microscopy with respect to the interaction of various parasites with host lymphoid organs, namely the bone marrow, thymus, lymph nodes, spleen and the mucosa‐associated lymphoid tissue, and present a view into possible future applications.